Suicide versus Accidental Death by Autoerotic Asphyxiation in a Patient Receiving Intravenous Ketamine for Depression - Weleff, Jeremy; Bryant, Kelly; Kovacevich, Alexsandra; Barnett, Brian S. (Case Reports in Psychiatry, 2022)
Background. Clinical trials have demonstrated that subanesthetic intravenous ketamine exerts antidepressant effects lasting a week or longer postinfusion, as well as antisuicidal effects starting approximately 4 hours postinfusion and lasting 72 hours or longer. These findings have generated considerable enthusiasm within psychiatry. However, reports of treatment-emergent suicide attempts and completed suicides in some patients receiving ketamine or the ketamine enantiomer esketamine have begun to emerge. Here, we contribute to the small literature on suicide-related adverse events and ketamine with an unusual case of a patient who died either by suicide or accidental death via autoerotic asphyxiation approximately four days after a ketamine infusion. Case Presentation. The patient was a 28-year-old man with major depressive disorder, generalized anxiety disorder, panic disorder, obsessive compulsive disorder, autism spectrum disorder without intellectual disability, attention deficit hyperactivity disorder, hypothyroidism, low testosterone, and sleep apnea referred for management of treatment resistant depression. His depression briefly remitted with ketamine, and suicidality briefly disappeared. However, these improvements were short-lived. Four days after his seventh and final scheduled ketamine infusion, the patient was found dead, presumably due to autoerotic asphyxiation. Interestingly, ketamine use has been reported in association with autoerotic asphyxiation. However, given our patient’s recent severe suicidality, methods of his past suicide attempts, and family history of suicide, death from suicide seems more likely. Discussion. Here we consider the possibility of whether ketamine may have contributed to the patient’s possible suicide, either via a direct worsening of his suicidality or psychological withdrawal following cessation of treatment, given recent concerns about psychological withdrawal's potential role insuicides following esketamine treatment. Conclusions. Though we are uncertain about the patient’s cause of death, this case provides an opportunity to highlight important gaps in our understanding of the suicide-related risks of subanesthetic intravenous ketamine treatment for mood disorders and suicidality.